Coronary plaque characteristics associated with major adverse cardiovascular events in atherosclerotic patients and lesions – a systematic review and meta-analysis. (3rd October 2022) - Gallone, G; Bellettini, M; Bruno, F; Scudeler, L; De Filippo, O; Iannaccone, M; Baldetti, L; Kwon-Koo, B; Pontone, G; Depaoli, A; Libby, P; Stone, G W; et al.
Abstract: Background: The clinical value of high-risk coronary plaque characteristics (CPCs) to inform intensified medical therapy or revascularization of non-flow-limiting lesion remains uncertain. Purpose: We performed a systematic review and meta-analysis to study the prognostic impact of CPCs on patient-level and lesion-level major cardiovascular adverse events (MACE). Methods: We systematically reviewed MEDLINE, EMBASE, and the Cochrane database for studies evaluating the association of CPC with patient-level and lesion-level MACE. CPCs included high plaque burden, low minimal lumen area, thin cap fibroatheroma, high lipid core burden index, low attenuation plaque, spotty calcification, napkin ring sign, or positive remodelling. Results: Thirty studies (21 retrospective, 9 prospective) with 30, 369 patients were included. CPCs were evaluated by invasive intravascular techniques in 9 studies (optical coherence tomography=4, intravascular ultrasound imaging=3, near-infrared spectroscopy intravascular ultrasound imaging=2) and by coronary computed tomography angiography (CCTA) in 21 studies. CPCs significantly predicted patient-level and lesion-level MACE in both unadjusted and adjusted analyses. For each CPC, the risks were higher for lesion-level (HR range 3.2–16.8) as compared with patient-level MACE (HR range 1.8–4.1). Accuracy was modest to good for most CPCs at the patient-level (AUC for MACE ranging between 0.53 and 0.84) and moderate to good for most CPCs at the lesion-level (AUC for MACE ranging between 0.71 and 0.83). Plaques with more than one CPC had the highest accuracy for lesion-level MACE (AUC 0.87, 95% CI 0.84–0.90). The pooled sensitivities of CPCs for lesion-level MACE ranged between 40% and 63% and specificities between 73% and 98%. As the pooled prevalence of CPCs among plaques was low (3% to 28%), the estimated positive predictive values for lesion-level MACE were modest (range 1% to 26%). Conclusions: CCTA and intravascular imaging characterization of CPCs identifies high-risk atherosclerotic plaques that place lesions and patients at risk for future MACE, albeit with modest sensitivity and positive predictive value (PROSPERO identifier: CRD42021251810). Funding Acknowledgement: Type of funding sources: None.